Iowa RBA, September 30-October 2, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for September 30-October 2, 1996. Highlights of the update include sightings of up to 50 White-winged Scoters, a Red-necked Phalarope, and an immature Sabine's Gull. Also of note were sightings of Merlins in multiple locations, 30 late Broad-winged Hawks, and an albino Red-tailed Hawk. Also included are handwritten notes for the next week's update with sightings of a Peregrine Falcon, a Thayer's Gull, and a Dunlin. Epson - sheet feed/flatbed